Challenges in Environmental Science/Engineering and fate and innovative treatment/remediation of emerging pollutants. (April 2022) - Jegatheesan, Veeriah; Shu, Li; Rene, Eldon R.; Lin, Tsair-Fuh
Abstract : Solid waste Management: There are two articles in this section. Shi et al. (2021) investigated the unbalanced status and multidimensional influences of municipal solid waste management in Africa. It was identified that economic growth, urbanization and geographical location are the most critical factors influencing the unbalanced statue of MSW management in Africa.